The engineering of TBBPA-degrading synthetic microbiomes with integrated strategies - Tong Wu; Sheng-Zhi Guo; Yi Zhang; Xi-Ze Zhao; Cong-Guo Ran; Feng-Lan Liu; Run-Hua Wang; De-Feng Li; Hai-Zhen Zhu; Cheng-Ying Jiang; Xi-Hui Shen; Shuang-Jiang Liu (npj Biofilms and Microbiomes)
Abstract The capability to understand and construct synthetic microbiomes is crucial in biotechnological innovation and application. Tetrabromobisphenol A (TBBPA) is an emerging pollutant, and the understanding of its biodegradation is very limited. Here, a top-down approach was applied for the enrichment of TBBPA-degrading microbiomes from natural microbiomes. Ten keystone taxa correlated to TBBPA degradation and their co-occurrence interactions were identified by the dissection of the degrading microbiomes. Those keystone taxa were targeted and cultivated, and the genomic information was obtained by genome sequencing of strains and metagenomic binning. The keystone bacterial strains showed efficient degradation of TBBPA, and L-amino acids were important co-metabolic substrates to promote the degradation. Guided by this knowledge, a bottom-up approach was applied to design and construct a simplified synthetic consortium SynCon2, that consisted of four strains. The SynCon2 demonstrated efficient TBBPA degradation activity and soil bioremediation. Our study demonstrates the importance of the application of multiple tools in understanding the functions of microbiomes and provides an integrated top-down and bottom-up strategy for the construction of synthetic microbiomes with various applications.